2022
DOI: 10.1097/qai.0000000000002984
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Implementation for HIV Pre-exposure Prophylaxis Based on an Updated Consolidated Framework for Implementation Research: A Systematic Review

Abstract: Supplemental Digital Content is Available in the Text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 45 publications
1
24
0
Order By: Relevance
“…Third, this analysis focused on the provider-level outcomes within the CFIR domain, Characteristics of Individuals, and was conducted only in non-PrEP clinics. Previous work from our group and others have shown numerous CFIR constructs relevant to PrEP implementation [ 14 , 43 ], including inner and outer setting factors that were not assessed in this analysis. Additional work is needed to examine provider-level and other successful pathways for PrEP implementation, including within clinics that already provide PrEP.…”
Section: Discussionmentioning
confidence: 99%
“…Third, this analysis focused on the provider-level outcomes within the CFIR domain, Characteristics of Individuals, and was conducted only in non-PrEP clinics. Previous work from our group and others have shown numerous CFIR constructs relevant to PrEP implementation [ 14 , 43 ], including inner and outer setting factors that were not assessed in this analysis. Additional work is needed to examine provider-level and other successful pathways for PrEP implementation, including within clinics that already provide PrEP.…”
Section: Discussionmentioning
confidence: 99%
“…Even fewer participants (39%) had ever discussed PrEP with their friends. Social communication about PrEP has proven to be a challenge in many settings due to PrEP-related stigma in many parts of the world [8]. For example, studies have suggested some of the judgmental beliefs attributed to people interested in PrEP – e.g., beliefs that equate PrEP with promiscuity, risk-taking, shame [41, 42].…”
Section: Discussionmentioning
confidence: 99%
“…While transfeminine adults in our sample showed high interest in taking LAI-PrEP, it is necessary for future studies aiming to inform PrEP implementation strategies to ascertain what transfeminine adults know about LAI-PrEP, including attitudes and beliefs about LAI-PrEP and how to best deliver it to their communities and social groups [8]. This includes understanding key health communication strategies such as efficacy messaging and framings about LAI-PrEP that resonate with other health priorities among communities of transfeminine adults such as access to hormones and gender-inclusive providers [47].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They first co-coded eight transcripts to become familiar with the coding constructs which were discussed with a third team member (JDS), who is experienced in using CFIR 2.0 for qualitative coding. 40 The two authors then independently coded 18 and 19 transcripts each and convened to check all codes, discuss questions that arose, and collaboratively determine the final code. Coding was confirmed by a third researcher (JDS), and any disagreements were discussed prior to finalizing the codes.…”
Section: Qualitative Analysismentioning
confidence: 99%